Water permeation in gas and liquid phases through organosilica membranes: A unified theory of reverse osmosis, pervaporation, and vapor permeation. (14th December 2022) - Moriyama, Norihiro; Nagasawa, Hiroki; Kanezashi, Masakoto; Tsuru, Toshinori
Graphical abstract: Highlights: Organosilica membrane showed stable and high flux during RO, PV, and VP at 150 °C. Generalized pore-flow (g-PF) model was proposed for porous membranes. Based on g-PF model, activity-based permeance was consistent across RO, PV, and VP. RO, PV, and VP experiments verified the consistency of activity-based permeance. g-PF model quantitatively predicts permeation for different adsorption properties. Abstract: Reverse osmosis (RO), pervaporation (PV), vapor permeation (VP), and gas separation (GS) are the possible permeation modes for molecular separation via membranes. In the present study, the relationship among them was formulated based on thermodynamics and verified via experiments. Water permeation via RO, PV, and VP was performed at a constant temperature of 150 °C and at a transmembrane pressure of 100 kPa using a recently developed hydrothermally stable organosilica membrane. This allowed an accurate evaluation of the permeance obtained from RO, PV, and VP, which confirmed the formulated model. In addition, the effect of concentration in the membrane pores was further included in the model, which successfully predicted the permeance of not only water but also methanol and hydrogen under different levels of pressure. The present study provides a general understanding of permeation and enables estimation of the performances of RO, PV, VP, and GS.